Dynamic response analysis for submerged floating tunnel due to fluid-vehicle-tunnel interaction. (15th October 2018) - Lin, Heng; Xiang, Yiqiang; Yang, Ying; Chen, Zhengyang
Abstract: To analyze the dynamic behavior of a submerged floating tunnel (SFT) subjected to moving vehicle loads in an ocean current environment, a theoretical analysis model is proposed. The SFT is simplified as a beam on an elastic foundation, the moving vehicle is modeled as a spring-mass lump, and the current effect is considered as a combination of lift force, inertial force, and hydraulic resistance directly acting on the SFT. The governing equations are solved by the modal superposition method. A finite element method is developed to evaluate the results. The impact effects of the vertical displacement and the bending moment are used to analyze the dynamic responses of the SFT. The effects of some key parameters, such as the current velocity, the buoyancy-weight ratio (BWR), and the inclined angle of the tethers are also investigated. The results show that the behaviors of the structure are amplified under the fluid-vehicle-tunnel interaction. Furthermore, the current and the vehicle velocity will directly affect the impact responses of the SFT by changing the forces on the structure. The BWR and the inclined angle of the tethers will change the vibration characteristics of the SFT and affect the inside state of the structure. Highlights: The model of SFT subjected to moving vehicle load under ocean current environment is proposed. The current effect is regarded as the lift force, inertial force and hydraulic resistance in the model. A FEM is developed to evaluate the responses of the SFT due to fluid-vehicle-tunnel interaction. The effect of the current velocity, the buoyance-weight ratio, and the inclined angle of the tether are studied.